Pengembangan Aplikasi Perpustakaan Berbasis Web untuk Peningkatan Kualitas Sirkulasi Pustaka di SMAN 1 Jombang - Sulistyaningrum, Dwi Ratna; Setiyono, Budi; Arif, Didik Khusnul; Utomo, Daryono Budi; Lukitosari, Valeriana; Hanafi, Lukman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The library is a learning infrastructure that must be available in every school. Libraries provide information and knowledge needed by students. The development of technology and information is expected to have an impact, namely the efficiency and effectiveness of the implementation of work. One way is to change the manual system into a computer-assisted system supported by internet technology. In this community service activity, a web-based library application has been designed and built at SMAN 1 Jombang. Application development uses the Waterfall model which consists of 4 stages, namely system requirements analysis, system design, implementation, and maintenance. The library application is built using the Code Ignaiter framework with the Hypertext Pre-Processor (PHP) programming language while the database uses MySQL.The benefit of this application is to address the needs of students for book searches and book ordering, while for school library officers it manages the circulation of book borrowing and reporting. The result of community service that has been implemented is a Web-based library application at SMA Negeri 1 Jombang to improve the quality of library management.DOI:Â https://doi.org/10.26905/abdimas.v6i2.5173